Bronchopneumonia with Serious Sequelae in Children with Evidence of Adenovirus Type 21 Infection. Issue 5636 (11th January 1969) - Lang, W. R.; Howden, C. W.; Laws, Jocelyn; Burton, J. F.
Abstract : Twenty-five cases of severe pneumonitis occurring among children aged 3 to 18 months were observed in Auckland, New Zealand, in 1965. An apparent relationship was established between a uniform disease picture and recovery of adenovirus type 21. Two died, and of the survivors 60% had permanent lung damage, probably resulting from obliterative bronchiolitis. Twenty per cent. were left with proved bronchiectasis. The possible relationships of adenovirus pneumonia to malnutrition or a genetic factor on the one hand and to the development of bronchiectasis on the other are discussed.